2020
DOI: 10.20944/preprints202009.0124.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photoperiodic Response of in vitro <em>Cannabis sativa </em>Plants

Abstract: Most commercial Cannabis sativa L. (cannabis) genotypes are short-day plants and cultivators typically use a 12.0 h uninterrupted dark period to induce flowering; however, scientific information is lacking to prove this is the optimal dark period for all genotypes, and cultivar specific photoperiods may increase productivity. Tissue culture can be used for research requiring multiple treatments, proper replication, and in a controlled environment on a smaller scale compared to greenhouse and indoor facilities.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…Leaves on a mature plant are digitate with anywhere from 5 to 11 leaflets and have a long petiole, although during flowering, they often revert to producing lower numbers of leaflets [ 23 , 28 ]. Cannabis is predominantly a short-day plant, with flowering induced by 12- to 14-h photoperiods [ 29 ]; however, some photoperiod-insensitive cultivars have been developed. Male and female plants cannot easily be distinguished until flowers begin to appear [ 26 , 30 ].…”
Section: Botany and Taxonomy Of C Sativamentioning
confidence: 99%
See 1 more Smart Citation
“…Leaves on a mature plant are digitate with anywhere from 5 to 11 leaflets and have a long petiole, although during flowering, they often revert to producing lower numbers of leaflets [ 23 , 28 ]. Cannabis is predominantly a short-day plant, with flowering induced by 12- to 14-h photoperiods [ 29 ]; however, some photoperiod-insensitive cultivars have been developed. Male and female plants cannot easily be distinguished until flowers begin to appear [ 26 , 30 ].…”
Section: Botany and Taxonomy Of C Sativamentioning
confidence: 99%
“…The maintenance of mother plants also requires them to remain in a vegetative state. While this is easily accomplished for most genotypes, it presents challenges for day-neutral genotypes as they do not respond to photoperiod [ 29 ]. Perhaps of greatest importance, though, is that mother plants are susceptible to insects, pathogens, and viruses and can transmit these biotic factors to their cuttings and lead to problems during production.…”
Section: Current Production Practicesmentioning
confidence: 99%
“…The inflorescence of the Cannabis plant is a highly branched compound racemose inflorescence that contains a large number of meristematic regions [22]. Initial observations found that some Cannabis plants initiate flower development in vitro ( Figure 1C and E), and recently Moher et al [29] demonstrated that flowering could be reliably induced using a short-day photoperiod similar to what is observed in the field. As such, in vitro flowering plants represent an alternative approach to increase the number of meristems per plant to potentially increase the multiplication rate.…”
Section: Floral Reversion: An Alternate Micropropagation Approachmentioning
confidence: 68%
“…Leaves on a mature plant are digitate with anywhere from 5-11 leaflets and have a long petiole, although during flowering they often revert to producing lower numbers of leaflets [23,28]. Cannabis is predominantly a short-day plant, with flowering induced by 12 to 14-hour photoperiods [29], however, some photoperiod insensitive cultivars have been developed. Male and female plants cannot easily be distinguished until flowers begin to appear [26,30].…”
Section: Botany and Taxonomy Of C Sativamentioning
confidence: 99%
See 1 more Smart Citation